Risk Assessment by Pre-surgical Tractography in Left Hemisphere Low-Grade Gliomas - Ius, Tamara; Somma, Teresa; Baiano, Cinzia; Guarracino, Ilaria; Pauletto, Giada; Nilo, Annacarmen; Maieron, Marta; Palese, Francesca; Skrap, Miran; Tomasino, Barbara (Frontiers in Neurology, 2021)
Background: Tracking the white matter principal tracts is routinely typically included during the pre-surgery planning examinations and has revealed to limit functional resection of low-grade gliomas (LGGs) in eloquent areas. Objective: We examined the integrity of the Superior Longitudinal Fasciculus (SLF) and Inferior Fronto-Occipital Fasciculus (IFOF), both known to be part of the language-related network in patients with LGGs involving the temporo-insular cortex. In a comparative approach, we contrasted the main quantitative fiber tracking values in the tumoral (T) and healthy (H) hemispheres to test whether or not this ratio could discriminate amongst patients with different postoperative outcomes. Methods: Twenty-six patients with LGGs were included. We obtained quantitative fiber tracking values in the tumoral and healthy hemispheres and calculated the ratio (HIFOF - TIFOF)/ HIFOF and the ratio (HSLF – TSLF)/ HSLF on the number of streamlines. We analyzed how these values varied between patients with and without postoperative neurological outcomes and between patients with different postoperative Engel classes. Results: The ratio for both IFOF and SLF significantly differed between patient with and without postoperative neurological language deficits. No associations were found between white matter structural changes and postoperative seizure outcomes. Conclusions: Calculating the ratio on the number of streamlines and fractional anisotropy between the tumoral and the healthy hemispheres resulted to be a useful approach, which can prove to be useful during the preoperative planning examination, as it gives a glimpse on the potential clinical outcomes in patients with LGGs involving the left temporo-insular cortex .